Preparation of Industrial Noise Mapping and Improvement of Environmental Quality - Bozkurt, Tarık Serhat (Springer Science and Business Media LLC, 2021)
Environmental noise control is necessary for human health and auditory comfort conditions. In this respect, it is required that industrial noise should be kept under control and healthy living spaces should be obtained in residential areas. This paper aims to explain industrial noise control at urban and building scales. In this study, the strategic noise mapping process related to industrial activities in a line with the Environmental Noise Directive (END) was clarified. Besides this, what type of factors are effective in the industrial noise mapping process were defined, and important basic parameters, which are essential in the industrial noise mapping, were detailed. The preparation of the industrial noise mapping process was explained in detail. It was mentioned that the regions exposed to excessive noise should be defined according to the strategic noise map and improvement plans should be performed. Improvement methods that reduce excessive noise in living spaces are clarified and it was explained how the improvement of environmental quality can be acquired. In this regard, this paper gives information on industrial noise mapping and industrial noise control at the urban scale.
Keywords: Noise Pollution (PHT Zannin, Section Editor)